Teaching Methods of Spoken English — Taking Rural Areas in Southwest China for Example - Yiru Wang; Lei He (Journal of Advanced Research in Education, 2024)
Based on the theoretical knowledge of educational psychology and language specialization, and under the guidance of “Positive Psychology Theory”, this project develops a set of innovative spoken English programs for secondary school students that combines Wittgenstein’s “Language Game Theory” with positive psychology theory and the “Positive Psychology Theory”. The program is based on a new model of student-student interaction and teacher-led guidance to improve secondary school students’ English speaking ability through small group classes and a differentiated game program for the students. The program breaks the traditional spoken English teaching model, combines students’ physiological and psychological characteristics, and strives to promote students’ personalized development, help students achieve from passive reception to active participation, and effectively improve students’ English language skills; in addition, the program also provides assistance and reference for solving the uneven distribution of educational resources between urban and rural areas and promoting the revitalization of rural education.